AgrHyS: An Observatory of Response Times in Agro‐Hydro Systems. Issue 1 (29th November 2018) - Fovet, Ophélie; Ruiz, Laurent; Gruau, Gérard; Akkal, Nouraya; Aquilina, Luc; Busnot, Sylvain; Dupas, Rémi; Durand, Patrick; Faucheux, Mikael; Fauvel, Yannick; Fléchard, Chris; Gilliet, Nicolas; et al.
Abstract : Core Ideas: AgrHyS is a long‐term observatory of the agroecosystem. AgrHyS supports strongly interdisciplinary environmental research. AgrHyS offers an original experimental setup to explore the soil–groundwater–water–plants–atmosphere continuum. AgrHyS supports original and innovative techniques for environmental monitoring. The AgrHyS is a long‐term agro‐hydrological observatory dedicated to studying the processes controlling hydro‐chemical fluxes in headwater catchments in response to the effects of agricultural. AgrHyS is composed of instrumented catchments located in western France in a temperate oceanic climate that are characterized by shallow groundwater (<8 m deep) over crystalline bedrocks (granite or schist) and is dominated by intensive agriculture with farming. AgrHyS provides long‐term observations starting in 1990 and supports highly interdisciplinary studies that provide novel contributions to environmental sciences, including hydrology, geochemistry, agricultural and soil sciences, hydrogeology, bioclimatology, and ecology. Here we describe the observatory sites, observation strategy, data management policy, and data access. The objective is to show how AgrHyS has contributed to research in hydrological and environmental sciences through a review of major insights of the research. This analysis highlights the role of AgrHyS in linking, validating, and enriching successive and complementary projects conducted over the last 25 yr. The second objective is to invite new collaborations with a large scientific community for future research.